Embodied Consciousness
XIII, 229 p.
Keywords: This volume of essays combines research from neuroscience, conscious studies, methods of training performers, modes of creating a staged narrative, Asian aesthetics, and post-modern theories of performance in an examination of the relationship between consciousness and performance.